Creating working quality through effective leadership, implementation of organizational culture, condusive working enviroment, communication skill, and technology support (Research on several companies/agencies in Jabodetabek) - Muchtamim, Muchtamim (Central Community Development Journal, 2025)
This study examined the creation of work quality through the influence of effective leadership, organizational culture implementation, a conducive work environment, communication skills, and technology support. This research was conducted in several companies and agencies within Jabodetabek, involving employees across job levels, including Administrators, Officers, Assistant Managers, Managers, Senior Managers, and Directors. Data were collected via questionnaires distributed through Google Forms to the 97 respondents. Employing a quantitative approach, the analysis included validity, reliability, and classical assumption tests such as multicollinearity, normality, heteroscedasticity, autocorrelation, and determination tests. The results confirmed that all the data were valid (r > 0.312) and reliable (Cronbach’s alpha > 0.60). Multicollinearity was absent, as all variance inflation factor (VIF) values were below 10 with a tolerance above 10%. The data were normally distributed, and no heteroscedasticity was observed. Both partial and simultaneous tests indicated that the five independent variables positively influenced creative work quality, as evidenced by the significant t-tests, F-tests, and determination coefficients. The coefficient of determination showed contributions of 0.7% from Effective Leadership, 36.1% from Organizational Culture Implementation, 21% from a conductive work environment, 34.1% from Communication Skills, and 31.1% from Technology Support, with a combined influence of 47.9%. A Durbin-Watson value of 2.291 (>2) indicated no positive autocorrelation, but the results suggested a negative autocorrelation. Overall, the study concludes that effective leadership, strong organizational culture, supportive environments, communication skills, and technological integration significantly enhance creative work quality in the Jabodetabek corporate context.